Investigation of mitochondrial genomes of members of the order Batrachospermales (Rhodophyta) - Da Silva, Nadia M. Lemes [UNESP]; Crowell, Roseanna M.; Vis, Morgan I.; Chiasson, Wayne B.; Paiano, Monica o. [UNESP]; Lopes, Yasmin M. Silva [UNESP]; Necchi, Orlando JR. [UNESP] (Taylor & Francis, 2025)
Data on genome characteristics and phylogenomics are becoming more readily available for the Rhodophyta, especially from organelles. However, for the freshwater red algal order Batrachospermales, information is still scarce with only nine organellar genomes available from six genera. A total of 22 new mitochondrial genomes representing 13 genera were generated and combined with the previously published data. Based on this large mitogenome data set, this study aimed to: (i) describe the structural characteristics of the mitogenomes across the Batrachospermales and compare with other red algal mitogenomes; (ii) infer phylogenetic relationships among the Batrachospermales using a broad dataset of taxa and genes. We determined that structure of the mitogenomes showed little variation, particularly genome size (22,863–29,785 bp), total number of genes (39–49), protein-coding genes (22–27), and GC content (25.3–32.4%). The largest genomes were observed in three species of Paralemanea, which also had larger intergenic regions. Synteny among members of Batrachospermales was highly conserved with the exceptions of three species of Paralemanea having a group II intron in the cox1 gene and the five Kumanoa species having a small divergent region. Only three gene losses were detected in the mitogenomes of members of Batrachospermales and the gene content was otherwise similar to other orders of Nemaliophycidae. The phylogenomic analysis based on 17 concatenated genes showed two large groups within the Batrachospermales, which were also recovered in previous studies of single or multigene phylogenetic analyses. The existence of two groups can have taxonomic implications to be considered in future studies.
Keywords: Freshwater red algae; genome structure; mitogenome; organellar genome; phylogenomics